ASPEK PENDIDIKAN KARAKTER DALAM PUISI HAMKA - Nani Solihati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstractThis study aims to describe character education values in HAMKA’s poems. It used the qualitative descriptive method. The data sources were HAMKA’s 11 poems in hisbooks Kenang-kenangan 70 Tahun Buya HAMKA and Kenang-Kenangan Hidup. The data werecollected by reading the content and meaning of each poem carefully and recording them.They were analyzed by the qualitative descriptive technique using Miles and Huberman’smodel consisting of research focus identification, data reduction, data analysis anddisplay, and inference making. The results show that HAMKA’s poems contain charactereducation values that include: (1) religiosity, (2) honesty, (3) hard work, (4) autonomy, (5)nationalism spirit, (6) love of the homeland, 7) social care, and (8) responsibility. Throughhis poems HAMKA tried to convey meaningful messages about the giving of guidanceto the reader to become a whole person with characters in the dimensions of heart, mind,body, feeling, and intention.Keywords: character education, poems, HAMKA